The effect of politicization on protest participation in non-democracies: the case of Hungary - Susánszky, Pál; Borbáth, Endre (Social science quarterly, 2025)
Politicization - the expansion of conflict in the political system - is often assumed to be associated with high levels of participation. Yet, this is not necessarily the case, especially in contexts of democratic backsliding. This study investigates how politicization of protest events affects individuals’ willingness to participate in protests, using Hungary as a most likely case. We examine three causal mechanisms that may mediate this effect: perceived risks of participation, political efficacy, and public support. Empirically, we rely on a pre-registered survey experiment conducted in August 2024. To operationalize politicization, we manipulated the issue's salience, the polarization of positions presented, and the number of actors involved in the protest. Our findings challenge the prevailing assumption by demonstrating that increasing politicization leads to lower levels of protest participation. In addition, causal mediation analysis shows that this demobilizing effect is primarily due to reduced perceived political efficacy and expected public support.
Zuerst veröffentlicht: 22. Oktober 2025
Gesehen am 27.01.2026